Analisis Tingkat Pengetahuan dan Personal Hygiene Dengan Kejadian Pediculosis Capitis di Pesantren Binaul Ummah Kabupaten Bantul - Nurcahyati, Feby Indah; Rangkuti, Ahmad Faizal (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Background: Pediculosis capitis is an ectoparasite infestation of the species pediculus humanus capitisthat lives on the human scalp and can cause various problems for sufferers. Transmission is divided intotwo, namely through direct and indirect contact. Personal hygiene and level of knowledge are risk factorsfor pediculosis capitis. The purpose of this study was to determine the relationship between the level ofknowledge and personal hygiene with the incidence of pediculosis capitis among female students at theBinaul Ummah Islamic Boarding School, Bantul, DIY.Methods: The design used in this study was an observational analytic capproach cross sectional. Thesampling technique used in this study was a technique total sampling of55 female student. The results wereanalyzed by univariate and bivariate with the chi square test.Results: The most characteristic of respondents was 13 years old (36.4%) and the highest class was classVIII (41.8%). Santriwati who have a low level of knowledge (56.4%) and personal hygiene is not good(63.6%). The incidence ofpediculosis capitis positivewas 74.5%. The results of thestatistical test for the chisquare level of knowledge p value = 0.034 and personal hygiene p value = 0.028, which means p value<0.05.Conclusion: There is a relationship between the level of knowledge and personal hygiene with theincidence of pediculosis capitis in students of the Binaul Ummah Islamic boarding school, Bantul, DIY.